Khảo sát khả năng ức chế ăn mòn của thép CT3 của bốn dẫn xuất amit từ axit béo tổng hợp C8-C18 - Kha, Đinh Văn; Nghiêm, Nguyễn Thế; Thuận, Ngô Thị; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2014)
Inhibition ability of mild steel corrosion of 4 amides (RCONH2(marked as A4), RCONH–CH2–CH2OH (marked as A5), RCON(CH2–CH2OH)2(marked as 6b) and RCONH–(CH2)2–NH–COR (marked as 7c) prepared as derivatives from aliphatic acid oxidatively synthesized from n- paraffin of Vietnam crude oil, has been examined by electrochemical methods. The corrosion test has been performed in chloride 3% solution at room temperature. The inhibition efficiency has been evaluated through corrosion potential Ecor, corrosion current icor and some other corrosion parameters. It is found that derivative 7c has the best inhibition ability